Acceleration mechanism of void development in concrete riprapped seawalls. Issue 3 (3rd July 2019) - Pamuk, Aykut; Sato, Shinji; Okabe, Yumi
ABSTRACT: The mechanism of void development inside the backfill of a concrete riprapped seawall was investigated through laboratory experiments and numerical modeling. Laboratory experiments have been conducted in an oscillatory flow tunnel. The leakage of sand through a small gap from an acrylic container has been examined with and without a large void in the container. The leakage rate was found to increase with the total void volume inside the container, thus suggesting the accelerated expansion of the void in the seawalls. In order to understand the role of pressure transmission in the backfill medium, a numerical model has been proposed based on the quasi-static assumption on Biot's consolidation equation using finite difference method in the one-dimensional domain. Results from the developed model using appropriate permeability and compressibility values demonstrated that the accelerated expansion of void could be developed by the compression of air void due to the transmission of oscillatory pressure through a gap.